THE CORRELATION BETWEEN GRAMMAR AND READING COMPREHENSION AND EFL LEANERS’ WRITING PERFORMANCE - Ilham Ilham (Universitas Muhammadiyah Mataram, 2017)
This study aims at investigating the correlation between grammar and reading comprehension and leaners ‘writing performance since there is a relationship among all of the skills. This study adopts multiple regression analysis to see the relationship among multiple variable. The sample of this study consist of 27 students of second semester English Department STKIP Pasundan Cimahi. The data of this study are collected via test. The test includes three parts: reading, grammar and students’ writing performance. The data is analysed through SPSS procedure. The multiple regression is run to measure the degree of relationship among variables. The finding shows that both grammar and reading cannot explain and predict writing performance. In other words, linguistic knowledge was not good predictor for writing task, since both grammar and vocabulary knowledge were not good predictor for writing performance.